Prevalence and Pattern of Congenital Coronary Artery Anomalies in Patients Undergoing Coronary Angiography at a Tertiary Care Hospital - Abdul Latif, Muhammad Shahab Uddin Khalil, Sami Ullah, Muzdalfa Parvez, Hamid Ali Shah, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This research aimed to characterize the clinical presentation, frequency, and distribution of CAAs in people experiencing angiography. In this study, we reviewed the presence of CAAs in 4072 patients. Study design: Cross-section study Study Setting: Current research was conducted at Department of interventional cardiology, MTI- Hayat Abad Medical Complex, Peshawar from Ist July 2021 to 30th June 2022. Methods: The current research analyzed data from 4072 angiograms performed. The medical record of the patients was used to recruit the CAAs patient’s profile. Angelini's categorization was used to categorise the coronary anomalies and two interventional cardiologists reviewed each coronary angiography separately, and in the event of a discrepancy, a senior cardiologist was contacted to achieve a consensus. GE 520 and GE 2100 were used for the coronary angiogram. Operators have the option of using either a radial or femoral incision. Results: Finding of the CAAs was found in 103 cases of CAAs (a prevalence of 2.5%). According to the data, the average age of the patients was 59.64±13.73. Of them, 89 (2.19%) individuals had anomalous coronary origin and/or course, 9 (0.2%) had intrinsic coronary arterial system abnormalities, 3 (0.07%) had anomalous coronary termination, and 2 (0.04%) had a single coronary artery. Overall, 36 individuals (0.44%) were found to have an aberrant right coronary artery (RCA), with the RCA emerging from the left coronary sinus; this was followed by 54 patients (1.3%) who lacked a left main trunk and instead had a distinct origin for the LAD and LCX. Practical implication: Our understanding of CAAs has considerably improved from the development of novel diagnostic techniques, although the majority of the data available today comes from case reports and small case series. Further research is needed to fill the knowledge gap regarding the clinical effects of CAAs and their prognosis because epidemiological data are taken from studies conducted in other countries. Conclusion: Overall, 2.5 percent of research participants had congenital coronary abnormalities. The highest prevalence was found in anomalies origin and course. This study's prevalence of CAAs was comparable to that of other research, although the distribution of abnormalities was a little bit different. Keywords: Congenital Coronary Artery Anomalies, Coronary Angiography, Prevalence, Pattern